AB0405 Factors associated with lupus nephritis in a highly admixed population. (23rd January 2014) - Pérez-Fernández, J. L.; Amaya-Amaya, J.; Molano-González, N.; Mantilla, R.-D.; Rojas-Villarraga, A.; Anaya, J.-M.
Abstract : Background: Lupus nephritis (LN) is one of the most serious complications of systemic lupus erythematous (SLE). Multiple clinical and serological risk and protective factors for LN have been identified in Caucasians. Objectives: The aim of this study was to examine associated factors for LN in a new cohort of Latin American patients. Methods: The study included 310 consecutive SLE patients (91% female, median age at onset: 38 years) followed at a single-center. The population means estimated autosomic Amerindian, European and African admixture are 26%, 63.5% and 10.6%, respectively and the means estimated X-chromosome admixture are 43.5%, 45.3% and 11.2%, respectively. LN was defined by the presence of active urinary sediment or proteinuria, nephritic or nephrotic syndrome, or a positive renal biopsy (ISN/RPS). Data were examined by bivariate and multiple correspondence analyses. Environmental exposure (i.e., ever smoke, coffee consumption, silicone implants, organic solvents, hair dye, and pesticides exposure) and cutaneous involvement (i.e., photosensitivity, oral ulcers, malar rash, urticary, discoid lupus, subacute lupus, and skin and oral ulcers) were examined by latent trait analysis using two-parameters logistic model through item response theory. Logistic regression analysis was done to assess the factors associated with LN. Interaction among biologically plausible variables was also evaluated. Results: Nephritis was present in 46.5% of patients. Environmental factors (AOR: 1.64, 95%CI: 1.02-2.71, p=0.04), dyslipidemia (AOR: 18.1, 95%CI: 4.58-89.2, p<0.001), pleural effusion (AOR: 3.1, 95%IC: 1.45-6.99, p=0.004) and psychosis (AOR: 5.9, 95%CI: 1.40-31.4, p=0.02) were positively associated with LN. In contrast, the presence of Sjögren's syndrome (SS, AECG 2002) disclosed a protective factor (AOR: 0.23, 95%CI: 0.06-0.73, p=0.01). In addition, dyslipidemic patients with short duration of disease and those with pleural effusion with cutaneous involvement exhibited a higher risk for LN. The coefficient of determination was 27%, indicating the multifactorial causation of LN. Conclusions: Risk and protective factors for LN were confirmed in this admixed SLE population. These results may serve to define public health policies aimed to tight control the modifiable risk factors for LN. The search for additional factors for LN including genetics and epigenetics will improve our knowledge of this critical condition. Admixed populations can be a powerful resource for elucidating those factors. References: Contreras G, et al. Am J Phys Anthropol. 2006; 69:1846–51. Rojas W, et al. Kidney Int. 2010; 143(1):13-20. Disclosure of Interest: None Declared